The Aztec Gods in Blended-Space: a Cognitive Approach to Ritual Time - Dehouve, Danièle (Journal of cognition and culture, 2019)
By applying diverse approaches to study the Aztec gods, light can be shed on different aspects of their personalities. In this article the cognitive theory of conceptual blending, developed by Fauconnier and Turner, is applied. In this perspective the functioning of the human mind is viewed as being grounded on the constant blending of mental spaces, a process that, in turn, makes new mental spaces emerge. After briefly reviewing the attempts to apply this theory to the ritual domain in general, I consider two types of Aztec rituals, one dedicated to the rain god Tlaloc, and the other to Xochiquetzal, the goddess of seduction. I show the importance of the compression of time in the blending process that condenses three moments: mythical time, ritual time and the immediate future. The capability of the gods to subvert the lineal passage of time and to compress past, present and future stands out as a one of the chief characteristics highlighting the advantages found by applying Blending-Theory.